2021
DOI: 10.1002/hed.26931
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of health and treatment decisions in head and neck cancer

Abstract: Background: This study compares select social determinants of health (SDOH) with treatment modality selection and treatment completion in head and neck cancer (HNC) patients, to better understand disparities in health outcomes.Methods: A retrospective cohort study of HNC (n = 1428) patients was conducted. Demographic and disease-specific variables were recorded, including treatment modality selection and completion. Data were analyzed using twosample t tests, chi-square, and Fisher's exact tests. Results: Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Malignant tumors of the head and neck disproportionately affect low-income communities: patients with low SES are at increased risk of developing HNC and have a poorer prognosis . These results emphasize the intersectionality of social drivers of health: low HL in patients with HNC may further exacerbate preexisting health disparities, specifically in vulnerable patients …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Malignant tumors of the head and neck disproportionately affect low-income communities: patients with low SES are at increased risk of developing HNC and have a poorer prognosis . These results emphasize the intersectionality of social drivers of health: low HL in patients with HNC may further exacerbate preexisting health disparities, specifically in vulnerable patients …”
Section: Discussionmentioning
confidence: 98%
“…[51][52][53] These results emphasize the intersectionality of social drivers of health: low HL in patients with HNC may further exacerbate preexisting health disparities, specifically in vulnerable patients. 34,51,54,55 Alternatively, it has been suggested that low HL may be a potential mediator of health disparities in patients with low SES and among certain ethnic and racial populations. Several studies have shown that low HL mediates the relationship between race or low SES and health outcomes and medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research indicates that non-English speakers are less likely to follow multidisciplinary team treatment recommendations [ 7 ] resulting in poorer outcomes [ 8 ]. National Institute for Health and Care Excellence (NICE) guidelines [CG138] for improving the experience of care for people using adult NHS services' state that healthcare providers have a responsibility to ensure all patients have access to interpretation services when this is required [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…SCC accounts for 90–95% of all head and neck cancer cases ( 8 ). Other less common types include salivary gland tumors, lymphomas and sarcomas ( 9 ).…”
Section: Introductionmentioning
confidence: 99%